2021
DOI: 10.3390/life11040332
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics, ROS, and Cell Signaling: A Blended Overview

Abstract: Mitochondria are key intracellular organelles involved not only in the metabolic state of the cell, but also in several cellular functions, such as proliferation, Calcium signaling, and lipid trafficking. Indeed, these organelles are characterized by continuous events of fission and fusion which contribute to the dynamic plasticity of their network, also strongly influenced by mitochondrial contacts with other subcellular organelles. Nevertheless, mitochondria release a major amount of reactive oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 134 publications
2
73
0
Order By: Relevance
“…Since the recognition of mitochondrial diseases in humans in 1962 [ 1 ], numerous studies have elucidated the physiological and pathological significance of mitochondrial function. Mitochondria are intracellular organelles, which are present in almost every cell in the body and are responsible for the production of energy in the form of adenosine triphosphate (ATP) [ 2 , 3 ]. Thus, in patients with mitochondrial diseases, organs that are dependent on mitochondrial production for energy may be damaged [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the recognition of mitochondrial diseases in humans in 1962 [ 1 ], numerous studies have elucidated the physiological and pathological significance of mitochondrial function. Mitochondria are intracellular organelles, which are present in almost every cell in the body and are responsible for the production of energy in the form of adenosine triphosphate (ATP) [ 2 , 3 ]. Thus, in patients with mitochondrial diseases, organs that are dependent on mitochondrial production for energy may be damaged [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mitochondrial ROS plays a prominent role in inducing inflammatory mediators and immune regulation events in various inflammation-related diseases [38][39][40]. Mitochondrial ROS affects inflammatory cytokine production via the activation of MAPK, including extracellular signal-regulated kinase, c-Jun n-terminal kinase, and p38 [41]. Based on this evidence, we investigated the mechanisms underlying the activities of these extracts in HNEpCs and found that GJW and GJE significantly inhibited the upregulation of mitochondrial ROS and periostin in IL-4/IL-13-treated HNEpCs in a dose-dependent manner, mirroring the effect of MitoTEMPO because these extracts function as mitochondria-targeted antioxidants (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The LIP contributes to the intracellular ROS level through the Fenton reaction, where the Fe 2+ is converted into Fe 3+ by H 2 O 2 , producing hydroxyl radicals [183]. The excess of ROS acts as intermediates in several signaling pathways [184] and can promote podosome formation [71].…”
Section: Inorganic Nanoparticles and Invadosome Dynamicmentioning
confidence: 99%